2017
DOI: 10.1093/jrr/rrx012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of 50 Hz magnetic field exposure on DNA damage and cellular functions in various neurogenic cells

Abstract: Epidemiological studies have indicated a possible association between extremely low–frequency magnetic field (ELF-MF) exposure and the risk of nervous system diseases. However, laboratory studies have not provided consistent results for clarifying this association, despite many years of studies. In this study, we have systematically investigated the effects of 50 Hz MF exposure on DNA damage and cellular functions in both neurogenic tumor cell lines (U251, A172, SH-SY5Y) and primary cultured neurogenic cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
0
11
0
2
Order By: Relevance
“…Nevertheless, based on the hint that the cellular response was dependent on the cell type, prior to starting our experiments, we reviewed the state of the art of specific studies performed with glioblastoma cells models [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Why Should We Study the Effects Produced By Non-ionizing mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, based on the hint that the cellular response was dependent on the cell type, prior to starting our experiments, we reviewed the state of the art of specific studies performed with glioblastoma cells models [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Why Should We Study the Effects Produced By Non-ionizing mentioning
confidence: 99%
“…After doing this search, we realized that most studies performed with glioblastoma models varied only time of exposure [ 30 , 32 , 33 , 34 , 35 , 36 , 39 ] and almost no one studied the effects produced by different frequencies [ 30 ].…”
Section: Why Should We Study the Effects Produced By Non-ionizing mentioning
confidence: 99%
See 1 more Smart Citation
“…Some similar studies showed insensitivity to ELF-MF in biological cells [ 12 ]. They found no evidence that ELF-MF could cause DNA damage in vivo or in vitro, as in human lens epithelial cells or neurogenic cells [ 13 16 ]. One hour of continuous and 75 min of intermittent (15 min power field on/15 min power field off) exposure indicated that MFs at power frequency may not cause DNA damage in cardiomyocytes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, McNamee et al did not detect any significant increase in DNA damage in rat or mouse brain cells after 2 h MF exposure (0–2 mT, 60 Hz) (McNamee et al, 2005). An in vitro study conducted by Su et al investigated both neurogenic tumor cell line cells and primary cultured neurogenic cells from rats exposed to 50 Hz MFs at 2 mT for up to 24 h, and no DNA damage effects were observed (Su et al, 2017). Using different methods of exposure, Focke et al found that intermittent (5 min on/10 min off) but not continuous exposure of human primary fibroblasts to a 50 Hz MF at 1 mT induced a slight but significant increase of DNA fragmentation (Focke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%